Environmental and occupational cancer in Argentina: a case-control lung cancer study Cáncer ambiental y ocupacional en Argentina: estudio de un caso-control en cáncer de pulmón - Elena Matos; Marta Vilensky; Paolo Boffetta (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1998)
The main objective of this study was to analyze the risks for lung cancer associated with occupational exposures in a developing country where lung cancer is the first cause of mortality from cancer in men. The study involved 200 men with lung cancer and 397 hospital controls. The OR for current smokers was 8.5, whereas former smokers displayed an OR of 5.3. The fraction attributable to smoking was 85%. Statistically significant high ORs were observed for employment in the alcoholic beverages industry (4.5, 95% CI:1.02-20.2), sawmills and wood mills (4.6, 95% CI:1.1-18.4), chemicals/plastics (1.8, 95% CI:1.04-3.2), and pottery, glass, or mineral manufactures (3.4, 95% CI:1.1-10.6). Other high, but not statistically significant, risks were observed for employment in leather shoe industry and repair (2.1, 95% CI:0.8-5.4), rubber industries (3.4, 95% CI:0.9-12.4), metal workers, including welders (1.9, 95% CI:0.8-4.4), motor vehicle mechanics (2.0, 95% CI:0.9-4.2), workers in cleaning services (1.9, 95% CI:0.8-4.5), and for workers in agriculture (2.4, 95% CI:0.9-6.0). Although some of the present results may be due to chance, most are consistent with those of previous investigations in other countries. El objetivo principal de este estudio fue analizar los riesgos para cáncer de pulmón asociados con exposiciones ocupacionales, en un país en vías de desarrollo donde el cáncer de pulmón es la primera causa de mortalidad por cáncer en hombres. El estudio incluyó 200 hombres con esta patología y 397 controles hospitalarios. El OR para fumadores actuales fue 8,5, mientras que los ex-fumadores mostraron un OR de 5,3. La fracción atribuible al hábito de fumar fue de 85%. Se observaron riesgos estadísticamente significativos para: empleo en la industria de bebidas alcohólicas (4,5, 95% CI:1,02-20,2), aserraderos (4,6, 95% CI:1,1-18,4), industrias químicas, plásticos (1,8, 95% CI:1,04-3,2), cerámica, loza, vidrio o productos minerales no metálicos (3,4, 95% CI:1,1-10,6). Otros riesgos elevados, pero sin significación estadística, fueron encontrados para la industria y el trabajo en la reparación del calzado de cuero (2,1, 95% CI:0,8-5,4), la industria de la goma (3,4, 95% CI:0,9-12,4), el grupo de metalúrgicos que incluye los soldadores (1,9, 95% CI:0,8-4,4), los mecánicos de automotores (2,0, 95% CI:0,9-4,2), los trabajadores en servicios de limpieza (1,9, 95% CI:0,8-4,5) y los trabajadores agrícolas (2,4, 95% CI:0,9-6,0). Si bien algunos de los presentes resultados pueden ser debidos al azar, la mayoría son consistentes con los obtenidos en investigaciones previas en otros países.